Effect of Model-Eliciting Activities (MEAs) Approach on Students' Mathematical Communication Skills - Rema Anggralia; Ria Deswita; Selvia Erita; Mhmd. Habibi; Putra, Aan (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2019)
Abstract This study aims to determine the effect of the Model-Eliciting Activities (MEAs) approach towards the students’ mathematical communication skills. This research is a quasi-experimental study by the nonequivalent posttest-only control group design. This research population was the eighth-grade students in SMP Negeri 2 Sungai Penuh that consisted of seven groups. The sample in this study consisted of two groups, namely VIII C as an experimental group and VIII D as a control group selected by cluster random sampling technique. In the experimental group, the MEAs approach was done while the control group was done with conventional learning. The research instrument used to measure students’ mathematical communication skills was a subjective test. The data were analyzed using the independent t-test. The results of data analysis showed that there is an effect of MEAs approach towards the students’ mathematical communication skills. Keywords: Model-Eliciting Activities (MEAs) Approach, Mathematical Communication Skills